Concentration-Dispersal Strategies to Assist Geotourism Destination Planning: A Case Study of Ciletuh-Palabuhanratu UNESCO Global Geopark - Shandra Rama Panji Wulung; Rifki Rahmanda Putra; Raden Willy Ananta Permadi; Muhammad Iqbal Maulana (Journal of Indonesian Tourism and Development Studies, 2020)
This article aims to identify and design a spatial model of geotourism destinations based on concentration and dispersal strategies in Cisolok Geoarea, Ciletuh-Palabuhanratu UNESCO Global Geopark, Indonesia. This study uses a qualitative approach with primary and secondary data collection. Primary data collection was carried out through field observations at the Cisolok Geoarea and semi-structured interviews with people directly involved in the development of the Ciletuh-Palabuhanratu UNESCO Global Geopark. The positioning of spatial elements based on satellites uses the Global Positioning System (GPS) technology. In the meantime, secondary data carried out through literature studies on policy documents, planning, and previous research. The analytical method used in this study includes qualitative analysis, map analysis, and descriptive analysis. Stages of research were carried out through the process of input, management, plotting, and conversion of data and information obtained. This study found that Cisolok qualified as a geotourism destination with the support of eleven integrated spatial elements. The results of this study can be a strategy for the dispersal of tourists visiting the Ciletih-Palabuhanratu UNESCO Global Geopark, especially in Cisolok Geoarea.Keywords: Ciletuh-Palabuhanratu UNESCO Global Geopark, destination management, geotourism, tourism planning.